Increasing the adoption of conservation agriculture: A framed field experiment in Northern Ghana - Ambler, Kate; de Brauw, Alan; Murphy, Mike (Wiley, 2023)
Conservation agriculture techniques have the potential to increase agricultural production while decreasing CO2 emissions, yet adoption in the developing world remains low—in part because many years of continuous adoption may be required to realize gains in production. We conduct a framed field experiment in northern Ghana to study how incentives and peer information may affect adoption. Incentives increase adoption, both while they are available and after withdrawal. There is no overall effect of peer information, but we do find evidence that information about long-term adoption increased adoption, particularly when that information shows that yield gains have been achieved.